2013
DOI: 10.1007/s00423-013-1081-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of previous cardiovascular surgery on postoperative morbidity and mortality after major pulmonary resection for non-small cell lung cancer

Abstract: Major pulmonary resections for NSCLC can be performed safely in patients with previous cardiovascular surgical history who are fulfilling the common cardiopulmonary criteria of operability. Operative risk in this subpopulation is comparable to that in patients without cardiovascular comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Coronary artery disease was a predictor of postoperative mortality, which is in agreement with the results of Bernard et al who analyzed a cohort of 639 pneumonectomies and found that cardiovascular disease was predictive of postoperative mortality [ 10 ]. Senbaklavaci et al reported no differences in postoperative morbidity or mortality following major pulmonary resection for NSCLC between 31 patients with previous cardiovascular disease and 167 patients with no cardiovascular disease history [ 26 ]. However, only 5 patients in the subgroup of 31 patients with previous cardiovascular disease underwent pneumonectomies; thus the utility of the comparison of these findings to our own is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease was a predictor of postoperative mortality, which is in agreement with the results of Bernard et al who analyzed a cohort of 639 pneumonectomies and found that cardiovascular disease was predictive of postoperative mortality [ 10 ]. Senbaklavaci et al reported no differences in postoperative morbidity or mortality following major pulmonary resection for NSCLC between 31 patients with previous cardiovascular disease and 167 patients with no cardiovascular disease history [ 26 ]. However, only 5 patients in the subgroup of 31 patients with previous cardiovascular disease underwent pneumonectomies; thus the utility of the comparison of these findings to our own is limited.…”
Section: Discussionmentioning
confidence: 99%
“…For previous cardiac surgeries, Senbaklavaci et al showed that patients undergoing cardiovascular operation including coronary revascularisation did not show any difference in overall morbidity, postoperative pneumonia, prolonged air leak, atrial fibrillation or in-hospital mortality compared to patients without history of heart surgery ( 16 ). These findings are similar to our subgroup population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports document the surgical results of patients undergoing lung cancer surgery with cardiovascular comorbidities [ 16 19 ]. Takenaka et al [ 16 ] reported no increases in the postoperative morbidity and mortality rates and no influence on the long-term results, while Senbaklavaci et al [ 20 ] reported that a CVS history hardly increased morbidity and mortality after major lung resection. In contrast, Ambrogi et al [ 17 ] reported an increase in postoperative morbidity with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%